Kiai Leadership in Advancing Agribusiness Enterprises in Islamic Boarding Schools in Jambi Province - Nurusydiyati; Kasful Anwar; Lukman Hakim (International Journal of Post Axial: Futuristic Teaching and Learning, 2025)
This study explores the role of kiai leadership in the development of pesantren-based agribusiness in three Islamic boarding schools in Jambi Province: Pondok Pesantren Raudhatul Mujawwidin (Tebo), Pondok Pesantren Irsyadul Ibad (Batanghari), and Pondok Pesantren Al Muttaqin (Muaro Jambi). The findings reveal that the kiai holds a central and strategic position, not only as a spiritual leader but also as a key driver in designing, implementing, and sustaining agribusiness initiatives. Through a participative and visionary leadership style, the kiai integrates religious values with economic practices, fosters student engagement, builds external partnerships, and promotes pesantren self-reliance. Despite facing challenges such as limited land and resources, the kiai’s efforts have made agribusiness an integral part of pesantren education and community empowerment. This research highlights the importance of enhancing leadership capacity and institutional collaboration to strengthen the role of pesantren in sustainable economic development.